MKRN3 Interacts With Several Proteins Implicated in Puberty Timing but Does Not Influence GNRH1 Expression - Yellapragada, Venkatram; Liu, Xiaonan; Lund, Carina; Känsäkoski, Johanna; Pulli, Kristiina; Vuoristo, Sanna; Lundin, Karolina; Tuuri, Timo; Varjosalo, Markku; Raivio, Taneli (Frontiers in Endocrinology, 2019)
Paternally-inherited loss-of-function mutations in makorin ring finger protein 3 gene (MKRN3) underlie central precocious puberty. To investigate the puberty-related mechanism(s) of MKRN3 in humans, we generated two distinct bi-allelic MKRN3 knock-out human pluripotent stem cell lines, Del 1 and Del 2, and differentiated them into GNRH1-expressing neurons. Both Del 1 and Del 2 clones could be differentiated into neuronal progenitors and GNRH1-expressing neurons, however, the relative expression of GNRH1 did not differ from wild type cells (P=NS). Subsequently, we investigated stable and dynamic protein-protein interaction (PPI) partners of MKRN3 by stably expressing it in HEK cells followed by mass spectrometry analyses. We found 81 high-confidence novel protein interaction partners, which are implicated in cellular processes such as insulin signaling, RNA metabolism and cell-cell adhesion. Of the identified interactors, 20 have been previously implicated in puberty timing. In conclusion, our stem cell model for generation of GNRH1-expressing neurons did not offer mechanistic insight for the role of MKRN3 in puberty initiation. The PPI data, however, indicate that MKRN3 may regulate puberty by interacting with other puberty-related proteins. Further studies are required to elucidate the possible mechanisms and outcomes of these interactions.